Predıctıon Of The Skeletal Age By Usıng The Cervıcal Vertebral Dımensıons - Sönmez Fıratlı; Evren Öztaş (Galenos Yayinevi, 1996)
The purpose of this study is to develop a new method to predict the skeletal age by using the dimentional changes of the cervical vertebrae due to the growth and development on the routinely taken lateral cephalometric radiographs before the orthodontic treatment. The lateral cephalometric and hand wrist radiographs obtained at the same time of the 206 subjects (112 girls and 94 boys) various malocclusions aged from 9 to 15 were examined. Only the subjects with a difference of 0.5 years or smaller between chronological and skeletal age were included. The skeletal ages of the subjects were determined by the same investigator by using the Greulich-Pyle atlas at the beginning of the study. Nine ratios was obtained by using the 13 milimetric measurements which were performed on images of the first, second, third, and fourth cervical vertebrae on the lateral cephalometric radiographs. The correlation coefficients (r) were calculated between the each of the nine ratios, and skeletal age, in girls and boys. In girls, 7 of the 9 ratios showed statistically significant correlations (-0.32 r 0.80), and in boys 6 of the ratios showed statistically significant correlations (0.26 r 0.68). Followingly, stepwise multiple regression analysis was performed to determine the useful parameters for assessing the skeletal age. The skeletal ages of all subjects were calculated by using the results of the multiple regression analysis and then the skeletal ages calculated by using the ratios of the cervical vertebrae were compared with the skeletal ages according to the hand-wrist radiographs. Then the harmony of the predictions obtained from the cervical vertebrae to the hand-wrist skeletal ages was examined. The skeletal ages derived from the cervical vertebrae is relatively lower than the skeletal ages according to hand wrist radiographs. Analysis for correctly determining the skeletal ages ranged between %60-65 in girls and %61-68 in boys with a deviation of 1 year. This situation may be the result of the disharmony between the hand wrist radiographical standarts of Greulich-Pyle and the standarts of Turkish children.